Approach to China in the EU’s Strategic Vision (2016‒2023) - Denis V. Leushkin; Nikita G. Samoilov (Современная Европа)
The goal of the paper is to identify the main stages of the formation of the ambivalent image of the PRC in the European discourse, as well as the causes and factors that determined the transformation of the approach to China in official documents and statements, including the points of view of a number of European think tanks. The first stage is related to the emergence of prerequisites for the deterioration of bilateral relations due to the intensification of economic contradictions. The second one is linked to Beijing’s dual role as a partner and competitor becoming mainstream in Europe in the context of the deteriorating relations. Finally, the third stage is associated with the growing EU’s ambitions in ensuring international and regional security, in particular those highlighted in the Strategic Compass, and negative attitude of the EU towards the Chinese stance on the Russo-Ukrainian conflict. The authors use a world-systems approach, focusing on the influence of external economic factors on the development of the European discourse towards China. The research relies on the analysis and comparison of the EU European documents, official statements made by heads and representatives of the European institutions, as well as publications provided by experts and analytical centres studying relations between the EU and PRC. The consolidation of China’s contradictory image as both partner and rival in the official European discourse and expert community is quite natural. It is related to the aggravation of the crisis of the world-system itself, transformation of the world order, as a result, the actualisation of economic disagreements, which can be illustrated by the EU’s trade deficit with China. Brussels’ modern approach to Beijing fits into the logic of the confrontation between “democracies” and “autocracies” – the conflict with China is publicly covered not as an economic rivalry, but as an “existential struggle” between different political systems articulated in ideological terms. The authors believe that such an internally contradictory approach to China will remain dominant in the face of the above-mentioned issues.